ZEB1 turns into a transcriptional activator by interacting with YAP1 in aggressive cancer types - Lehmann, Waltraut; Mossmann, Dirk; Kleemann, Julia; Mock, Kerstin; Meisinger, Chris; Brummer, Tilman; Herr, Ricarda; Brabletz, Simone; Stemmler, Marc; Brabletz, Thomas (Nature Communications, 2016)
Early dissemination, metastasis and therapy resistance are central hallmarks of aggressive cancer types and the leading cause of cancer-associated deaths. The EMT-inducing transcriptional repressor ZEB1 is a crucial stimulator of these processes, particularly by coupling the activation of cellular motility with stemness and survival properties. ZEB1 expression is associated with aggressive behaviour in many tumour types, but the potent effects cannot be solely explained by its proven function as a transcriptional repressor of epithelial genes. Here we describe a direct interaction of ZEB1 with the Hippo pathway effector YAP, but notably not with its paralogue TAZ. In consequence, ZEB1 switches its function to a transcriptional co-activator of a 'common ZEB1/YAP target gene set', thereby linking two pathways with similar cancer promoting effects. This gene set is a predictor of poor survival, therapy resistance and increased metastatic risk in breast cancer, indicating the clinical relevance of our findings.
EVALuna2:10213